GE_GERICHTE P/16852/2016 vom 7. November 2018 - GE Cour de justice (2018)
IN DUBIO PRO REO ; DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL) ; CONCOURS D'INFRACTIONS ; PEINE D'ENSEMBLE | CP.139.al3; CEDH.6.al2; CP.144.al3; CP.49.al1; CP.47; CP.89.al6